2020
DOI: 10.1002/ange.202009397
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Discrete CHA Zeolite Nanocrystals without Organic Templates for Selective CO2 Capture

Abstract: Small‐pore zeolites such as chabazite (CHA) are excellent candidates for the selective separation of CO2; however, the current synthesis involves several steps and the use of organic structure‐directing agent (OSDA), increasing their cost and energy requirements. We report the synthesis of small‐pore zeolite crystals (aluminosilicate) with CHA‐type framework structure by direct synthesis in a colloidal suspension containing a mixture of inorganic cations only (Na+, K+, and Cs+). The location of CO2 molecules i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 31 publications
(45 reference statements)
1
11
0
Order By: Relevance
“…29 Si MAS NMR analysis for the K04 and K17 series are presented in Figure 6c,d ), and 0 Al (Si[SiO] 4 ) species. [20] For the K17 series (Figure 6d), sample K17-1 shows similar results to the samples K04-3 and K04-5 while for samples K17-3 and K17-5 the different crystallographic Si environments can be observed and are similar to those of sample K04-7. The increased HT treatment from 3 h to 5 h does not result in any changes in the 29 Si NMR spectra for the K17 series, similar to the results shown for XRD and FTIR, thus confirming that fully crystalline CHA was obtained after 3 h. The Si/Al ratio of the fully crystalline samples K04-7 and K17-3 calculated by the Engelhardt and Michel equation is 2.1 (Table 1, S1).…”
Section: Spectroscopic Characterization Of Nanosized Cha Zeolitessupporting
confidence: 51%
See 3 more Smart Citations
“…29 Si MAS NMR analysis for the K04 and K17 series are presented in Figure 6c,d ), and 0 Al (Si[SiO] 4 ) species. [20] For the K17 series (Figure 6d), sample K17-1 shows similar results to the samples K04-3 and K04-5 while for samples K17-3 and K17-5 the different crystallographic Si environments can be observed and are similar to those of sample K04-7. The increased HT treatment from 3 h to 5 h does not result in any changes in the 29 Si NMR spectra for the K17 series, similar to the results shown for XRD and FTIR, thus confirming that fully crystalline CHA was obtained after 3 h. The Si/Al ratio of the fully crystalline samples K04-7 and K17-3 calculated by the Engelhardt and Michel equation is 2.1 (Table 1, S1).…”
Section: Spectroscopic Characterization Of Nanosized Cha Zeolitessupporting
confidence: 51%
“…In comparison, TEM analysis of the sample K17-3 shows discrete nanosized CHA crystals with sizes of less than 60 nm (Figure 3b) significantly smaller than the CHA reported in our previous work (~200 nm). [20] Rheometric analysis of the CHA samples from the K04 and K17 series are presented in Figure 4 showing the changes in the viscosity of the colloidal precursor suspension during the HT treatment. As shown in Figure 4a for sample K04-1, the viscosity of the colloidal suspension increases substantially from 2 cPs to 50000 cPs and remains high until 3 h of HT treatment due to the formation of micron-sized amorphous agglomerated aluminosilicate particles (Figure 2a).…”
Section: Macroscopic Characterization Of Nanosized Cha Zeolitesmentioning
confidence: 99%
See 2 more Smart Citations
“…Similarly, much attention has been paid to small pore zeolites since they are attractive candidates due to the shape and size of the porous structures ( Dusselier and Davis, 2018 ). High selectivity to CO 2 over CH 4 in small-pore zeolites such as CHA, MER, and RHO was observed ( Debost et al, 2020 ). It was also found that the CO 2 quadrupole moment has an impact, especially on cation-rich zeolites with a low Si/Al ratio, such as X zeolite, resulting in high capacity of CO 2 capture ( Sun et al, 2019 ).…”
Section: Catalytic Processes With Transition Metals On Zeolitesmentioning
confidence: 99%